Staged Closure of Giant Omphalocele using Synthetic Mesh - Parida, Lalit (EL-MED-Pub, 2014)
Giant omphalocele is difficult to manage and is associated with a poor outcome. A male newborn presented to our hospital with a giant omphalocele. We performed a staged closure of giant omphalocele using synthetic mesh to construct a silo and then mesh abdominoplasty in the neonatal period that led to a successful outcome within a reasonable period of hospital stay.